Safety and Outcome of Intravenous Thrombolysis in Stroke Patients on Prophylactic Doses of Low Molecular Weight Heparins at Stroke Onset. Issue 5 (May 2019) - Cooray, Charith; Mazya, Michael; Mikulik, Robert; Jurak, Lubomir; Brozman, Miroslav; Ringleb, Peter; Dixit, Anand; Toni, Danilo; Ahmed, Niaz
Abstract : Background and Purpose—: There are limited data on intravenous thrombolysis treatment in patients with ischemic stroke who have received prophylactic doses of low molecular weight heparins (LMWHs). We aimed to evaluate the safety and outcomes of intravenous thrombolysis treatment in stroke patients taking thromboprophylactic doses of LMWH. Methods—: We analyzed 109 291patients treated with intravenous thrombolysis, recorded in the Safe Implementation of Treatments in Stroke International Thrombolysis Register between 2003 and 2017 not taking oral anticoagulants or therapeutic doses of heparin at stroke onset. One thousand four hundred eleven patients (1.3%) were on prophylactic LMWH for deep venous thrombosis prevention. Outcome measures were symptomatic intracerebral hemorrhage, parenchymal hematoma, death within 7 days and 3 months, and functional dependency at 3 months. Results—: Patients on LMWH were older, had more severe strokes, more prestroke disability, and comorbidities than patients without LMWH. There was no significant increase in adjusted odds ratios (aOR) for symptomatic intracerebral hemorrhage (aOR, 1.02 [95% CI, 0.48–2.17] as per Safe Implementation of Treatments in Stroke -MOST, aOR, 0.95 [0.59–1.53] per ECASS II]), nor for 7-day mortality (aOR, 1.14 [0.82–1.59]), in the prophylactic LMWH group. The LMWH group had a higher aOR for 3-month mortality (aOR, 1.94 [1.49–2.53]) and functional dependency, aOR, 1.44 (1.10–1.90). Propensity score analysis matching patients on baseline characteristics removed differences between groups on all outcomes except 3-month mortality. Conclusions—: Intravenous thrombolysis in patients with acute ischemic stroke on treatment with prophylactic doses of LMWH at stroke onset is not associated with an increased risk of symptomatic intracerebral hemorrhage or early death. Abstract : Supplemental Digital Content is available in the text.